FORMING MORAL CHARACTERS OF STUDENTS WITH THE MEDIA OF MUSIC - Shahida Rahmatullayevna Mahkamova (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the criteria and requirements for homework, homework assignments and their assessment in fine arts classes.